CONTROLS ON THE CRETACEOUS AND CENOZOIC EVOLUTION OF SEAWATER COMPOSITION, ATMOSPHERIC CO2 AND CLIMATE - Wallmann K. (My University, 2001)
A new box model for the global carbon-calcium-strontium cycle is developed to simulate the evolution of Cretaceous and Cenozoic seawater and atmosphere. The model accounts for carbon masses in ocean and atmosphere, in carbonate, in particulate organic carbon (POC), and in the mantle. Major processes considered in the model are mantle degassing and hydrothermal fluxes, alteration of oceanic crust, chemical weathering, metamorphism of carbonates, carbonate accumulation, carbonate turnover in subduction zones, and the turnover of POC. Model outputs are partial pressure of CO2 (pCO2), seawater pH, concentrations of Ca, Sr, and HCO3 in seawater as well as the C and Sr isotopic composition of seawater and marine carbonates. A comprehensive review of current fluxes is given to define the flux equations and parameters. Secular trends recorded in marine carbonates are used to constrain the remaining open model parameters. The model includes a new parameterization of silicate weathering considering the contribution of young volcanic deposits. The weathering of these deposits consumes a large fraction of volcanically-released CO2 and maintains moderate pCO2 levels during periods of intense mantle degassing and volcanic/tectonic activity. Further negative feed-back is provided by POC burial which is coupled to pCO2-dependent weathering rates. The model produces high Ca concentrations during the Cretaceous and a strong increase in both pH and carbonate alkalinity during the late Cenozoic. Moreover, it predicts high atmospheric CO2 and surface temperatures for the mid-Cretaceous and early Cenozoic and low values for the late Cenozoic icehouse world thus suggesting a close coupling between climate and pCO2. Finally, it demonstrates that the mid-Cretaceous greenhouse was caused by enhanced volcanic/tectonic activity and confirms that the late Cenozoic cooling has been induced by an increase in silicate weatherability caused by enhanced mountain building and erosion.
Keywords: Cretaceous; Cenozoic; Cenozoic; Mesozoic::Cretaceous; Мезозой::Меловая; Кайнозой